2011
DOI: 10.1177/229255031101900410
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Incision Choice On Outcomes of Nipple-Sparing Mastectomy Reconstruction

Abstract: The periareolar incision results in a higher rate of nipple necrosis following NSM and immediate tissue expander breast reconstruction. Using the lateral or inframammary incision reduces the incidence of nipple necrosis and may help improve overall reconstructive and cosmetic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 27 publications
4
45
0
Order By: Relevance
“…37,38 This rate is also consistent with the significant rise in mastectomy flap necrosis at our institution since the adoption of nipple-sparing mastectomy and direct-to-implant reconstruction. Despite the higher risk of mastectomy flap necrosis, these newer techniques allow for better aesthetic outcomes, often in a single stage, and are therefore preferred by patients and surgeons.…”
Section: Discussionsupporting
confidence: 81%
“…37,38 This rate is also consistent with the significant rise in mastectomy flap necrosis at our institution since the adoption of nipple-sparing mastectomy and direct-to-implant reconstruction. Despite the higher risk of mastectomy flap necrosis, these newer techniques allow for better aesthetic outcomes, often in a single stage, and are therefore preferred by patients and surgeons.…”
Section: Discussionsupporting
confidence: 81%
“…However, NAC and skin flap ischemia and necrosis can occur and result in morbidity to the patient. Previous studies have reported various patient, clinical, and surgical factors, such as age, smoking history, and type of surgical incision, that are associated with ischemic and necrotic complications after NSM (2,9,14,15,19,21,22). Our study is unique in that it addresses vascular features on pre-operative MRI that are predictive of ischemic and necrotic complications.…”
Section: Discussionmentioning
confidence: 67%
“…Several factors associated with NAC and skin flap ischemia and necrosis have been reported, including age, body mass index (BMI), smoking history, hypertension/diabetes mellitus, pre-operative radiation therapy, oncologic indication for NSM, breast volume, type of incision, reconstruction approach, and NAC involvement with areola flap thickness less than 5 mm (2,9,14,15,19,21,22,25). To our knowledge, however, there are no published studies on the vascular supply to the breast, as characterized by pre-operative MRI, and its association with NAC and skin flap ischemia and necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Donovan et al suggested that this approach was associated with higher incidence of positive or close anterior margin, which may affect LR risk (208). A lateral incision also appears to have a low risk for nipple necrosis (209). Most data suggest a higher risk for necrosis with a periareolar incision, so this should be avoided when possible (210).…”
Section: Expanding Indications For Nipple-sparing Mastectomymentioning
confidence: 99%